DIVERSE VOLCANISM IN SOUTHEASTERN GUATEMALA: THE ROLE OF CRUSTAL CONTAMINATION - Cameron B.I.; Walker J.A. (My University, 2006)
In the Central American arc, southeastern Guatemala hosts the most diverse volcanism. Large stratovolcanoes at the volcanic front (VF) form as a result of subduction of the oceanic Cocos plate beneath the continental Caribbean plate. Behind the volcanic front (BVF) volcanism, however, has undergone a fundamental change in eruptive style during the Quaternary from older, polygenetic central volcanism to younger, monogenetic cinder cone volcanism. Magmas that traverse the 40-45-kmthick crust in southeastern Guatemala are highly susceptible to crustal contamination. Consequently, mineral chemical data, whole-rock oxygen isotope, and light element geochemistry are used to investigate the relationship between edifi ce type and the magnitude of crustal contamination. The lack of systematic variation between compositions of phenocryst phases and host rocks strongly suggests that open system processes were operating. Moreover, phenocryst core compositions are generally out of equilibrium with host rock compositions. Olivine from BVF cinder cones deviate only slightly from the equilibrium line in comparison to the older behind the volcanic front (OBVF) central volcanoes and VF stratovolcanoes, suggesting less assimilation of crustal lithologies. Steep arrays on the δ18O-SiO2 diagram cannot be explained by crystal fractionation and favor the incorporation of 18O-enriched crustal rocks. Higher δ18O values in the OBVF central volcanoes and VF stratovolcanoes support the idea that larger, shallow magma bodies experienced greater amounts of crustal contamination. Regional extension in the Ipala Graben of southeastern Guatemala likely promoted short residence times in crustal reservoirs and small degrees of crustal assimilation for the BVF cinder cone magmas. © 2006 Geological Society of America.
Keywords: ARC MAGMAS; CRUSTAL ASSIMILATION; GEOCHEMISTRY; STABLE ISOTOPES; Quaternary; Cenozoic::Quaternary; Кайнозой::Четвертичная